Livedoid vasculopathy with mononeuritis multiplex associated with protein S deficiency mimicking systemic vasculitis - Vikramraj K Jain; Krishnamurthy Hegde; Renuka Panchagnula (Indian Journal of Rheumatology)
A 34-year-old female presented with recurrent ulcers over the bilateral lower limbs with mononeuritis multiplex. Possibilities considered were small-to-medium vessel vasculitis and vasculopathy. Skin biopsy was suggestive of livedoid vasculopathy (LV). Investigations revealed protein S deficiency. The patient was treated with anticoagulation and immunosuppression after which her symptoms improved. LV can be associated with thrombophilias, fibrinolytic disorders, autoimmune diseases, and malignancy. Polyarteritis nodosa closely mimics the disease and needs a deep dermal biopsy to differentiate.